A Comparative In Vitro Study of the Effects of Separate and Combined Products of Citrus e fructibus and Cydonia e fructibus on Immunological Parameters of Seasonal Allergic Rhinitis. (19th January 2012) - Baars, E. W.; Jong, M. C.; Boers, I.; Nierop, A. F. M.; Savelkoul, H. F. J.
Abstract : This paper examined the effects of the combined product, Citrus e fructibus/Cydonia e fructibus (Citrus/Cydonia; Citrus and Cydonia: each 0.01 g/mL), and separate products of Citrus (0.01 g/mL) and Cydonia (0.01 g/mL) on the immunological pathways involved in seasonal allergic rhinitis (SAR). Peripheral blood mononuclear cells (PBMCs) from five healthy and five grass pollen-allergic donors were isolated and analyzed in vitro after polyclonal and allergen-specific stimulation of T cells in the presence of the three extracts. The analyses demonstrated acceptable cell survival with no signs of toxicity. Citrus mainly had a selective effect on reducing allergen-specific chronic inflammatory (TNF-α; Citrus compared to Cydonia and Citrus/Cydonia: −87.4 (P < 0.001 ) and −68.0 (P < 0.05 ), resp.) and Th2 pathway activity (IL-5; Citrus compared to Cydonia: −217.8 (P < 0.01 ); while, both Cydonia and Citrus/Cydonia mainly affected the induction of the allergen-specific Th1 pathway (IFN-γ; Cydonia and Citrus/Cydonia compared to Citrus: 3.8 (P < 0.01 ) and 3.0 (P < 0.01 ), resp.). Citrus and Cydonia demonstrated different working mechanisms in the treatment of SAR and the combination product did not demonstrate larger effects than the separate preparations. Further effectiveness and efficacy studies comparing the effects of the products on SAR in vivo are indicated.